Neuronal differentiation of human mesenchymal stem cells using exosomes derived from differentiating neuronal cells. - Takeda, Yuji S.; Xu, Qiaobing. (Tufts University. Tisch Library., 2016)
Exosomes deliver functional proteins and genetic materials to neighboring cells, and have potential applications for tissue regeneration. One possible mechanism of exosome-promoted tissue regeneration is through the delivery of microRNA (miRNA) In this study, we hypothesized that exosomes derived from neuronal progenitor cells contain miRNAs that promote neuronal differentiation. We treated mesenchymal stem cells (MSCs) daily with exosomes derived from PC12 cells, a neuronal cell line, for 1 week. After the treatment with PC12-derived exosomes, MSCs developed neuron-like morphology, and gene and protein expressions of neuronal markers were upregulated. Microarray analysis showed that the expression of miR-125b, which is known to play a role in neuronal differentiation of stem cells, was much higher in PC12-derived exosomes than in exosomes from B16-F10 melanoma cells. These results suggest that the delivery of miRNAs contained in PC12-derived exosomes is a possible mechanism explaining the neuronal differentiation of MSC.